Perbandingan Cloud Computing Microsoft Onedrive, Dropbox, dan Google Drive - Irwan Agus; Fitriana Destiawati; Harry Dhika (Faktor Exacta, 2019)
Cloud Computing is one of the latest web-based information technology that provides services that are able to provide sources of information and services. Now with the development of mobile technology that supports and with the industrial revolution has supported mobile computing everywhere with cloud computing technology. The development of the cloud is very fast and there are many cloud facilities scattered today. This study analyzes Cloud Computing in a comparison of Microsoft OneDrive, Dropbox, and Google Drive so that users can distinguish and compare cloud computing and their respective uses. The results provide or describe the differences so that the use of the three cloud computing can be maximized.